Desafios, potencialidades e compromissos de uma experiência pedagógica para a formação cidadã: prática CTS construída a partir de uma ilha interdisciplinar de racionalidade sobre reciclagem do lixo urbano - SOUSA, Rogério Gonçalves de (2007)
The current sociocultural dynamics has led the education to the formation of critical and compromised citizens. Favoring this formation type, it is presented as an alternative for the Science Education the pedagogical practices called Interdisciplinary Rationality Islands (IRI) which based on the relationship among Science, Technology and Society (STS). In this work, I analyze an IRI under the theme the recycling of urban garbage developed on an youngsters and adult education class, using as analytical instruments a target log book annotations, questionnaires and works planned by students. The results highlighted some challenges imposed to the subjects involved such as the teaching process centered on the teacher, the organization of time, the adoption of an interdisciplinary practice on a disciplinary environment and the group work. Those aspects indicated the need to be committed with cooperation in the classroom with the establishment of a favorable environment for the cooperation in the classroom, the provide of human, audiovisual and material resources, the leave of the comfort zone and the responsibility with the own learning; besides all the above mentioned, it was also evidenced some aspects of learning potentialized by experience and related to the development of contents relevant to citizenship a such as a humanistic vision, the critical argumentation and the ecological citizenship view.